Checkpoint inhibitors as dual immunotherapy in advanced non-small cell lung cancer: a meta-analysis - Alifu, Muyesar; Tao, Min; Chen, Xiao; Chen, Jie; Tang, Kejing; Tang, Yubo (Frontiers in Oncology, 2023)
Introduction: Recent clinical trials have confirmed that anti-programmed cell death-1/ Ligand 1 (anti-PD-1/L1) combined with either anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) or anti-TIGIT antibodies (dual immunotherapy) produced significant benefits as first-line therapies for patients with advanced non-small cell lung cancer (NSCLC). However, it also increased the incidence of adverse reactions that cannot be ignored. Our study aims to explore the efficacy and safety of dual immunotherapies in advanced NSCLC. Methods: This meta-analysis ultimately included nine first-line randomized controlled trials. Efficacy was measured as the hazard ratio (HR) and 95% confidence interval (CI) for progression-free survival (PFS), overall survival (OS), and risk ratio (RR) for the objective response rates (ORR). Treatment safety was assessed by RR of any grade of treatment-related adverse events (TRAEs) and grade≥3 TRAEs. Results: Our results demonstrated that, compared to chemotherapy, dual immunotherapy shows durable benefits in OS (HR=0.76, 95%CI: 0.69-0.82) and PFS (HR=0.75, 95%CI:0.67-0.83), across all level of PD-L1 expression. Subgroup analysis also presented that dual immunotherapy resulted in improved long-term survival compared with chemotherapy in patients with a high tumor mutational burden (TMB) and squamous cell histology. However, compared with ICIs monotherapy, dual immunotherapy only showed advantages in PD-L1＜25% subgroup in terms of PFS. With regarded to safety, there was no significant difference in total TRAEs between the dual immunotherapy and chemotherapy groups. But, compared with ICIs monotherapy, dual immunotherapy significantly increased the incidence of any grade TRAEs and grade≥3 TRAEs. Conclusions: As for the efficacy and safety outcome that compared with standard chemotherapy, dual immunotherapy remains an effective first-line therapy for patients with advanced NSCLC. Furthermore, compared to single agent immunotherapy, dual immunotherapy is only considered for use in patients with low PD-L1 expression in order to reduce the emergence of resistance to immunotherapy.